Dampak Pendidikan Etika Bisnis dan Pendidikan Ekonomi Syariah terhadap Etika Bisnis (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2014)
This paper examines empirically the the differences in business ethics students who have attended the course of business ethics with students who do not follow business ethics education and the differences in business ethics students who have attended the course in Islamic economics students who do not follow sharia ekonimi education. The sample were 128 students. Data was collected using questionnaires that measured with a Likert scale and dummy. Analysis of data using independent paired t-test. The results showed that students who have attended the course of business ethics have different business ethics with students who do not follow business ethics education. In addition, students who have attended the course of Islamic economics has a different business ethics with students who do not follow Islamic economics education. Business ethics education and Islamic economics education can improve students' business ethics. Penelitian ini dilakukan untuk membuktikan secara empiris perbedaan etika bisnis mahasiswa yang telah mengikuti pendidikan etika bisnis dengan mahasiswa yang belum mengikuti pendidikan etika bisnis serta perbedaan etika bisnis mahasiswa yang telah mengikuti pendidikan ekonomi syariah dengan mahasiswa yang belum mengikuti pendidikan ekonimi syariah. Sampel penelitian adalah 128 mahasiswa. Data diukur dengan skala likert dan dummy. Analisis data menggunakan independent paired t-test. Hasil penelitian menunjukkan bahwa mahasiswa yang telah mengikuti pendidikan etika bisnis memiliki etika bisnis yang berbeda dengan mahasiswa yang belum mengikuti pendidikan etika bisnis. Selain itu mahasiswa yang telah mengikuti pendidikan ekonomi syariah memiliki etika bisnis yang berbeda dengan mahasiswa yang belum mengikuti pendidikan ekonomi syariah. Pendidikan etika bisnis dan pendidikan ekonomi syariah mampu meningkatkan etika bisnis mahasiswa.